The Physical Presence of Survivance in The Heirs of Columbus - Schaak, Hogan (Transmotion, 2020)
Critics attempt to make sense of the fantastic happenings in Gerald Vizenor’s The Heirs of Columbus (1991) by taking his plethora of theoretical claims, the pinnacle of which is a concept called “survivance,” and applying them to the novel. However, no one has considered that Heirs does not simply give body to Vizenor’s theory, but surpasses it, crafting and testing a new definition of “survivance.” I argue in this paper that Vizenor’s Heirs adds a new dimension of “survivance,” portrayed particularly in his character Stone. In this way, “survivance” moves beyond its generally agreed upon definition as personal and intellectual liberation from identity constraints in order to encompass physical and communal healing as well.